Preparation Model Of The Indicative Ceiling District In Support Of The Council Development Plan Case Study In The District Of Majalengka - Boy Tagajagawani (CV. Inara, 2021)
On the study models the preparation of the ceiling inidikatif district aims to get the standard model in the contrive pegu indicative districts in favor of a council development plan in the district of majalengka. Methodology this research uses a qualitative descriptive approach, with the primary data collection method and skuder through interviews and document study. The results of this study produced a model of a standard preparation of the indicative ceiling district as standard in musnyawarah development plan. The results of this model can be used as a policy area majalengka regency in the preparation of development plans to the budget-setting process in the indicative ceiling district in accordance with the proportional region respectively in the district of majalengka.